The Influence of One’s Own Database on the Accuracy of Forecasting Future Movements of Investment Portfolio Value - vesna Trančar (Naše gospodarstvo/Our economy, 2017)
The main purpose of this article is to present the test results of the hypothesis that the use of one’s own (and foreign) database (used by investment portfolio managers to create indicators of individual stock analyses) has an effect on the accuracy of forecasting future movements of investment portfolio value. In addition to the use of different indicators and methods of stock analysis, the creation of an optimal investment portfolio requires assessment of the suitability and adequacy of the database used in investment portfolio managers’ decision- making process; in other words, it is necessary to determine which stocks are to be included in the specific investment portfolio and which are not. The problem of the selection and use of different databases is linked to the question of determining the importance of numerous relevant elements when creating an optimal investment portfolio.